A systematic review and meta-analysis on utilizing anti-CD19 chimeric antigen receptor T-cell therapy as a second-line treatment for relapsed and refractory diffuse large B-cell lymphoma - Asghar, Kanwal; Zafar, Maryam; Holland, Eva; Abduljabbar, Ali Bin; Albagoush, Sara A.; Asghar, Noureen; Sood, Akshat; Dufani, Jalal M.; Thirumalaredy, Joseph; DeVrieze, Bradley; Tauseef, Abubakar; Husnain, Muhammad (Frontiers in Oncology, 2024)
Inconsistent results observed in recent phase III trials assessing chimeric antigenic receptor T (CAR-T) cell therapy as a second-line treatment compared to standard of care (SOC) in patients with relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL) prompted a meta-analysis to assess the effectiveness of CAR-T cell therapy in this setting. Random-effects meta-analysis was conducted to pool effect estimates for comparison between CAR-T cell therapy and SOC. Mixed treatment comparisons were made using a frequentist network meta-analysis approach. Meta-analysis of three trials with 865 patients showed significant improvement in event-free survival (EFS: HR: 0.51; 95% CI: 0.27-0.97; I 2 : 92%), progression-free survival (PFS: HR: 0.47; 95% CI: 0.37-0.60; I 2 : 0%) with CAR-T cell therapy compared to SOC. Although there was a signal of potential overall survival (OS) improvement with CAR-T cell therapy, the difference was not statistically significant between the two groups (HR 0.76; 95% CI: 0.56 to 1.03; I 2 : 29%). Mixed treatment comparisons showed significant EFS benefit with liso-cel (HR: 0.37; 95% CI: 0.22-0.61) and axi-cel (HR: 0.42; 95% CI: 0.29-0.61) compared to tisa-cel. CAR-T cell therapy, as a second-line treatment, appears to be effective in achieving higher response rates and delaying the disease progression compared to SOC in R/R DLBCL.